2005
DOI: 10.2355/isijinternational.45.1095
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Olivine Primary Phase Field in the MgO-"FeO"-SiO2 System in Equilibrium with Metallic Iron

Abstract: Liquidus isotherms and phase equilibria have been measured in the olivine primary phase field of the MgO-"FeO"-SiO 2 system in equilibrium with metallic iron. Liquidus isotherms have been determined in the temperature range from 1523 to 1898 K. The tie lines between liquid and olivine solid solutions have been determined and the results were compared with those obtained in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This system describes a number of industrially important metallurgical slags. Previous studies [1][2][3] have shown that the presence of alumina can have significant effect on the liquidus temperatures of the slags. Data on the MgO-"FeO"-SiO 2 , 1) MgO-Al 2 O 3 -SiO 2 4) and "FeO"-Al 2 O 3 -SiO 2 5) subsystems have been described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This system describes a number of industrially important metallurgical slags. Previous studies [1][2][3] have shown that the presence of alumina can have significant effect on the liquidus temperatures of the slags. Data on the MgO-"FeO"-SiO 2 , 1) MgO-Al 2 O 3 -SiO 2 4) and "FeO"-Al 2 O 3 -SiO 2 5) subsystems have been described in detail.…”
Section: Introductionmentioning
confidence: 99%